Competition and Bank Liquidity Creation - Jiang, Liangliang; Levine, Ross; Lin, Chen (Journal of Financial and Quantitative Analysis, 2019)
We use a new identification strategy to assess whether an intensification of competition among banks increases or decreases the provision of a key banking service: liquidity creation. Although theory offers conflicting predictions about the impact of competition on liquidity creation, we find that regulatory-induced competition reduces liquidity creation. Consistent with a subset of models emphasizing that banks pushed toward insolvency reduce risk-taking activities, we discover that regulatory-induced competition reduces liquidity creation more among banks with less risk-absorbing capacity (e.g., less profitable banks).